Presentation of the Political Agenda in the News Programs of Lithuanian TV channels - Martyna Bajorinaitė; Marija Keršanskienė; Ligita Luščiauskaitė; Indrė Petronytė; Valdonė Rudenkienė; Donata Rukaitė; Valdemaras Šukšta (Žurnalistikos Tyrimai, 2019)
The authors of the article investigate how the parliamentary agenda is reflected in the agenda-setting. They determined the study period and examined how many decisions made in the Parliament are on the agenda of Lithuanian television channels. The study showed that the agenda of the Seimas of Lithuania occupies a very small part of the schedule of media topics. The researchers relied on journalistic criteria for the selection of information – novelty, relevance and conflict. According to them, the criteria by which journalists choose news are not very clear. Sometimes the selected news does not match any –novelty, relevance, or conflict criterion, and sometimes only one of them. However, the criterion of conflict should be considered dominant. Let‘s do it the premise that scandalous news is of most interest to the public. On the other hand, the fact that journalists take the news of a press release already prepared by the Parliament also partly explains the fact of non-compliance with the news selection criteria.